Starglam Hijab / Stella Joseph ... [et al.] - Joseph, Stella; Shaari, Nurul Najwa; Shuhaimi, Izzaty Nabila Arisya; Karim, Syakirah; Mohamad Juadzil, Nur Shaerah; Syamsul, Nur Suhana (2021)
Starglam Hijab is a boutique which has been opened at Taman Perindustrian Jaya, Petaling Jaya, Selangor. It is planned to open because we want to sell premium hijabs, inner scarf, brooches, and anything involved with the wearing of hijabs like accessories in a variety of types with powerful design to meet the demand of many women out there. We also provide a very high quality of material with extra quality of services where we provide the service of making hijab as what customers want with our brand. The idea of where the name of our boutique came from is we want our customer to shine like a beautiful stars and look glam whenever they are wearing our Hijab or any product from our brand. Most of our Hijab that we produce a really suitable in every situation especially when customer wants to wear it to any important event and it is really suitable for high income woman because we only produce hijab with high quality of material that is why our Hijab are premium.